A method for producing a biopolymer - Idris, Azni; Aljuboori, Ahmad H. Rajab; Abdullah, Norhafizah; Mohamad, Rosfarizan (2011)
The present invention relates to a method for producing a biopolymer, comprising the steps of providing a culture medium comprising a carbon source, a nitrogen source, and a plurality of mineral sources; inoculating the culture medium with a Aspergillus flavus with an inoculum size in a range of 0.2 to 10 % by volume; incubating the culture medium; filtering the culture medium, thereby separating the Aspergillus flavus and the biopolymer; purifying the biopolymer; wherein the carbon source to nitrogen source is in a molar ratio of 5:1, pH of the culture medium is 5 to 9, the temperature is 25 to 40ºC, inoculum size is 0.2 to 2 % by volume, shaking speed is 50 to 200 rpm, and culture time is 12 to 60 hours. A biopolymer produced having a molecular weight in a range of 2.466x104 to 2.68 x104 Dalton, a plurality of functional groups, a plurality of chemical elements, a sugar, a protein, a minimum flocculating efficiency of 90 % in a pH range of 3 to 7 and a temperature range of 10 to 100ºC.